Too many puppies - Brewster, Patience (New York : Scholastic, 1997)
A little girl looks forward to keeping all of Milly's puppies, but when they begin to make big demands on her, she changes her mind about them.
"Cartwheel Books."
"Kindergarten-grade 2"--Cover.
2.2
K-3
Keywords: Puppies -- Fiction; Dogs -- Fiction; Animals -- Infancy -- Fiction; Puppies -- Fiction; Dogs -- Fiction; Animal babies -- Fiction